Successful management of noncirrhotic hyperammonemia syndrome after kidney transplantation from putative Ureaplasma infection. Issue 5 (13th June 2020) - Cheema, Faiqa; Kutzler, Heather L.; Olowofela, Ayokunle S.; Maneckshana, Bejon T.; Rochon, Caroline; Sheiner, Patricia A.; Serrano, Oscar K.
Abstract: Noncirrhotic hyperammonemia (NCH) is a rare but often fatal complication of solid organ transplantation. We present a case wherein an infectious cause of NCH was suspected following kidney transplantation (KT) and the patient was promptly started on empirical antibiotic treatment which proved to be lifesaving. A 56‐year‐old Chinese woman with a past medical history of end‐stage renal disease secondary to ischemic nephropathy and cerebrovascular accident received a kidney from a 52‐year‐old brain‐dead donor with a Kidney Donor Profile Index score of 70%. She experienced immediate graft function and was discharged on post‐operative day (POD) 4. On POD 10, she presented with a fever, acute onset of confusion, and abdominal pain. Her mental status deteriorated and required emergent intubation. Empiric broad‐spectrum antibiotics were initiated. On hospital day 3, a serum ammonia was 889 μmol/L (normal <53 μmol/L). A urine sample was sent for Ureaplasma polymerase chain reaction (PCR) testing, and moxifloxacin and doxycycline were empirically started. Her ammonia rapidly normalized, and her mental status improved 48 hours after antibiotic initiation. She was extubated 5 days into treatment and was discharged after an 11‐day hospitalization. Following discharge, her urine test resulted positive for Ureaplasma parvum or Ureaplasma urealyticum DNA detection with the 16S rRNA gene amplification probe. Mental status changes and hyperammonemia in the first 30 days post‐KT should raise suspicion for NCH, and prompt empiric treatment with antimicrobials covering Ureaplasma and Mycoplasma should be considered.